Fragilidade, carga de comorbidades, intensidade de dor, incapacidade e qualidade de vida em idosos comunitários com dor lombar aguda: dados do estudo Back Complaints in the Elders (BACE) - Amanda Aparecida Oliveira Leopoldino (2016)
Introduction: Frailty is a prevalent manifestation in aging. Low back pain (LBP) is also prevalent in older people, but the relationship between frailty and clinical outcomes related to pain in patients with acute LBP is not well studied. In addition, as the population ages, individuals with multiple comorbid conditions become increasingly common in clinical practice. However, the effects of accumulated comorbidities in elderly patients with acute LBP have not been adequately investigated. Objectives: To establish whether frailty is associated to the intensity of pain, disability and quality of life (QoL) in older people with acute LBP and to investigate the association between the burden of comorbidities and prognosis of acute LBP in terms of pain and disability in this population. Method: In order to achieve the proposed objectives two studies were carried out. The sample of both studies consisted of 602 community-dwelling elderly (55 years) with acute LBP from the Back Complaints in the Elders (BACE)-Brazil Study. The first study involved a baseline cross-sectional analysis of BACE-Brazil, where participants were classified as robust, pre-frail or frail, using the frailty phenotype. Pain intensity was evaluated by the numerical pain scale (NSP 0-10), disability by the Roland-Morris Disability Questionnaire (RMDQ 0-24) and QoL through the Medical Outcomes Study (MOS) Short Form 36 - summarized in physical and mental components. Linear regression analysis was used to evaluate the relationship between frailty and pain intensity, disability, and QoL. The covariates of this study included age, sex, marital status, education, income, body mass index (BMI), depressive symptoms and comorbidities. The second study was a longitudinal analysis of BACE-Brazil data in the three-month follow-up. The comorbidity burden was assessed by the Self-administered Comorbidities Questionnaire (SCQ) and the intensity of pain and disability by the same instruments of the first study. Sociodemographic factors, BMI, level of frailty and depressive symptoms (Center for Epidemiological Studies - Depression - CES-D > 16) were considered possible confounders. Coefficients, p-values and the 95% confidence intervals (95% CI) were calculated in univariate and multivariate analyzes. The statistical package STATA 13 (Stata Corp LP, College Station, Texas) was used for all analyzes. For all tests we used a 0.05 significance level. Results: The mean ± standard deviation of age of the sample was 67.6 ± 7.0 years; (84.9% women). Using the frailty phenotype, 21.3% of the sample was identified as robust, 59.2% as pre-frail and 19.5% as frail. Compared to the robust group, the pre-frail and frail groups had significantly higher pain intensity and level of disability and worse QoL. After adjusting for demographic and clinical characteristics, frailty remained associated with disability and QoL (physical domain). In the second study, pain and disability levels were lower at the three-month follow-up, compared to baseline (p < 0.001). In the longitudinal analysis, the regression coefficient showed a significant association between the comorbidity load and the degree of disability as measured by the RMDQ, even after adjusting for possible confounders (0.25, 95% CI 0.13 to 0.38; p < 0.001). There was no association between the comorbidity load and pain at follow-up (0.06; 95% CI --0.01 to -0.14; p = 0.110). Conclusion: Our results demonstrate the importance of assessing the frailty phenotype in older patients with LBP in clinical practice. Undoubtedly, treatment approaches designed specifically for this clinical group need to be developed. Finally, in older patients with acute LBP, the burden of comorbidity was associated with worse prognosis for disability, but not with pain intensity.